1995
DOI: 10.1172/jci118118
|View full text |Cite
|
Sign up to set email alerts
|

Fibrates increase human apolipoprotein A-II expression through activation of the peroxisome proliferator-activated receptor.

Abstract: In view of the evidence linking plasma high density lipoprotein (HDL)-cholesterol levels to a protective effect against coronary artery disease and the widespread use

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
212
0
5

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 366 publications
(222 citation statements)
references
References 84 publications
5
212
0
5
Order By: Relevance
“…Previous studies had shown that fibrates increased human apoAII expression through activation of peroxisome proliferator-activated receptors ␣ in HCV-negative HepG2 cells. 34 We verified that peroxisome proliferator-activated receptors ␣ expression was maintained in HCV-positive HepG2 cells (data not shown). We also verified whether fenofibric acid could induce apoAII messenger RNA accumulation.…”
Section: Effect Of Fenofibric Acid On Apoaii Messenger Rna Accumulationmentioning
confidence: 60%
See 1 more Smart Citation
“…Previous studies had shown that fibrates increased human apoAII expression through activation of peroxisome proliferator-activated receptors ␣ in HCV-negative HepG2 cells. 34 We verified that peroxisome proliferator-activated receptors ␣ expression was maintained in HCV-positive HepG2 cells (data not shown). We also verified whether fenofibric acid could induce apoAII messenger RNA accumulation.…”
Section: Effect Of Fenofibric Acid On Apoaii Messenger Rna Accumulationmentioning
confidence: 60%
“…In order to clarify further the biological relevance of this interaction, we took advantage of the well-established increase in apoAII expression caused in HepG2 cells by fibrates. 34 We show here with the modulation of HCV core secretion brought about by the treatment with fenofibric acid of 2 independent clones of a HepG2 cell stably expressing the HCV core protein. Overall, our data identified apoAII as one of the cellular targets of HCV core protein and showed the direct impact of cellular lipid metabolism on HCV core protein secretion.…”
mentioning
confidence: 94%
“…Synthesis of apo A-I and apo A-II, the two major proteins of HDL, by the liver and intestine is the first step in HDL particle formation. PPAR-␣ activation by fibrates activates human apo A-I and apo A-II genes in the liver, leading to increased synthesis of these proteins (95)(96)(97)(98). A recent study (36) using rabbits expressing the human apo A-I transgene along with its PPRE showed an increase in human apo A-I mRNA and mass in response to fenofibrate treatment in the absence of any peroxisome-proliferative effect of the fibrate.…”
Section: Ppar-␣ Effects On Tg Ldl and Hdl Metabolismmentioning
confidence: 99%
“…18 In addition, the fenofibrate treatment caused small but not statistically significant changes in the expression of mouse Apoc3, Apoa2, Apoa5 and Apoe genes, as well as in other genes that are involved in the biogenesis and maturation of HDL such as Abca1, Lcat and Abcg1 (Table 1). Overall, the increase in HDL could not be accounted for by the upregulation of Apoa1 and Apoa2 as suggested previously 20,21 or attributed to the changes in several other genes implicated in the biogenesis of HDL.…”
Section: Discussionmentioning
confidence: 44%
“…9,10 Fibrates were shown to promote b-oxidation of fatty acids (FA) by upregulating various genes, including several genes of FA uptake and b-oxidation. [11][12][13][14][15][16][17][18][19] In rodents, fibrates downregulated the expression of Apoa1, 20 hepatic lipase 13 and lecithin cholesterol acyltransferase (Lcat) 15 genes and upregulated the expression of Apoa2 21 and phospholipid transfer protein (Pltp). 22 Previous studies of human ApoA-I transgenic Mice and rabbits indicated that fenofibrate increase plasma ApoA-I and HDL levels.…”
Section: Introductionmentioning
confidence: 99%